METOD OF PROJECTS IN FOREIGN PEDAGOGICAL THEORY AND PRACTICE: HISTORICAL ASPECT - Довгополова, Л. Д. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article deals with historical aspects of the project method formation in foreign pedagogical theory and practice, with emphasis on the stages of development of this method and refined periodization. In the article significant role of the project method in solving the problem of search and cognitive skills of students, forming their ability to construct their own knowledge, to see, formulate and solve a problem, that extends their abilities to achieve psychological maturity and promote successful entry into professional activities, is stressed. The author expresses his opinion that today the method of projects is one of promising methods of teaching, because it creates conditions for creative self-actualization of participants of educational process, increases their motivation to gain knowledge, contributes to the development of their intellectual abilities